A high-resolution stable isotopic record from the Junggar Basin (NW China) : implications for the paleotopographic evolution of the Tianshan Mountains - Charreau, Julien (2013)
This study presents high-resolution oxygen and carbon isotopic records of paleosol carbonates from fluvial sediments and lacustrine carbonates, sampled from the Jingou He and Kuitun He stratigraphic sections, located in the northern Tianshan piedmont. These sections expose remarkable outcrops of Junggar foreland basin sediments that have been previously dated by high-resolution magnetostratigraphy to between ∼23.6 and ∼1 Ma, and ∼10.5 and ∼3.1 Ma. A total of 216 samples of fluvio-lacustrine sediments were collected from which isotopic analyses yield δ18O (SMOW) values that range from 13.7‰ to 29.9‰ in the Jingou He section, and 16.3‰ to 21.0‰ in the Kuitun He section. δ13C (PDB) values range from −12.9‰ to 3.0‰ in the Jingou He section and from −7.8‰ to −4.0% in the Kuitun He section. δ18O values decrease between ∼25 and 23 Ma, and then remain relatively steady, with the exception of one period that contains samples with higher oxygen isotope values at ∼16 Ma. During the periods when there are samples that overlap in time from the Kuitun He and Jingou He sections, we observe a difference of ∼1.7% between values from the two locales. The δ13C values also decrease between ∼25 and 23 Ma, and then remain relatively steady until ∼10 Ma with, again, one short period of higher values at ∼16 Ma. Then, between ∼10 and 3.1 Ma, carbon isotope values progressively increase. We interpret that δ18O and δ13C isotopic values during lacustrine periods (∼25–23 Ma and ∼16 Ma) as largely controlled by evaporation and opening/closing of the lake to external inputs. We interpret the δ18O values of paleosol carbonate in the Junggar Basin to be influenced by the hypsometry of the high Tianshan range while the δ13C values may record the uplift history of the depositional area in the foreland basin itself as well as the isotopic composition of plants. Consequently, we conclude that the Jingou He and Kuitun He drainage basins in the Central Tianshan have remained at relatively unchanged elevations for the past ∼20 Ma. We also suggest that the elevation of the southern part of the foreland basin increased between ∼10 and ∼3.1 Ma, probably as a result of tectonic deformation in the piedmont and sedimentary filling of the sedimentary basin. The carbon isotope record remains relatively stable through time, and isotopic values suggest that there was little or no expansion of C4 plants in this region in the late Miocene.